Analysis of Students' Difficulty in Writing Beginnings in Class I Elementary School - Inayah Inayah; Eko Kuntarto; Khoirunnisa Khoirunnisa (Global READ Center, 2024)
The purpose of this research is to describe students' difficulties in writing beginnings and the factors that influence students' difficulties in writing beginnings. This research was carried out at SD Negeri 83/I Bajubang. This research uses a qualitative approach with a case study type of research. The data collection techniques in this research used observation, interview and documentation techniques. The Miles and Huberman model data analysis techniques are data reduction, data presentation and data verification. The results of the research show that students' difficulties in starting writing in grade I elementary school are that they do not know the letters of the alphabet, students are too slow in writing, write letters backwards, there are letters left behind when writing, the distance between words is unstable, and the student's sitting position when writing not quite right. Factors that influence students' initial writing difficulties are students' lack of interest and motivation in learning, lack of focus in learning, lack of mentoring and support from parents.